2017
DOI: 10.1111/1556-4029.13689
|View full text |Cite
|
Sign up to set email alerts
|

Certifying Death in the United States

Abstract: Accurately identifying death and its causes is integral to the compilation of mortality data and ultimately to the operation of the criminal justice and public health systems. A clear understanding of who is in charge of such processes is paramount to establishing the quality, or lack thereof, of the information provided in death certificates. Our study provides a comprehensive overview of all state statutes identifying death investigators charged with classifying and certifying death in the United States. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…However, our analysis is limited by our focus on only a single state and healthcare system. As such, these ndings may not represent patterns in other states' NVDRS systems or among all decedents, an especially notable limitation given the broad variability across states in medicolegal investigations (Oregon being among the states with a centralized medical examiner system; Hickman et al, 2004;Ruiz et al, 2018; US Department of Justice, 2019). Our analyses were also limited by a relatively small numbers of observations for analysis, making some of the estimated ORs unstable (i.e., wide con dence intervals) in our examination of patterns of sensitivity by decedent characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…However, our analysis is limited by our focus on only a single state and healthcare system. As such, these ndings may not represent patterns in other states' NVDRS systems or among all decedents, an especially notable limitation given the broad variability across states in medicolegal investigations (Oregon being among the states with a centralized medical examiner system; Hickman et al, 2004;Ruiz et al, 2018; US Department of Justice, 2019). Our analyses were also limited by a relatively small numbers of observations for analysis, making some of the estimated ORs unstable (i.e., wide con dence intervals) in our examination of patterns of sensitivity by decedent characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Vermont revealed that 51% of death certificates completed by non-medical examiners had major errors, and that certificates for hospital deaths were more error prone than those completed for residential deaths (59% vs. 39% errors) [25]. A nationally representative sample of older ­Americans who died while hospitalized found that there was significant disagreement between Medicare records and the assigned cause of death on certificates, and that the contributing nature of infections was under-reported [26]. Systems for certifying death vary by state – there are few standards, with official examiners sometimes having little or no medical expertise or training [27].…”
Section: Discussionmentioning
confidence: 99%
“…In FARS, toxicological testing was conducted by the respective medico-legal office such as the medical examiner or coroner [46,47]. Currently, 21 states and the District of Columbia have medical examiner systems, 9 have coroner systems, and 20 have mixed medical examiner and coroner systems responsible for certifying deaths [47,48]. The FARS database records up to three nonalcohol drugs per driver [42,49].…”
Section: Drug and Alcohol Testingmentioning
confidence: 99%